Identifying the Economic Potential Based on Leading Subsectors as the Foundation for Economic Development in Lampung Province: Identifikasi Potensi Ekonomi Berbasis Subsektor Unggulan Sebagai Pondasi Pembangunan Ekonomi Provinsi Lampung - Radinsyah Fauzi, Arya; Arivina Ratih Y.T; Resha Moniyana Putri (Goodwood Publishing, 2025)
Economic development is fundamentally aimed at improving people’s welfare. However, this goal has not yet been fully realized in Lampung Province. To support economic progress in the region, this study seeks to identify the province's leading sub-sectors. The research uses secondary data, specifically Gross Regional Domestic Product (GRDP) figures obtained from BPS (Statistics Indonesia) of Lampung Province. The analysis methods applied include Location Quotient (LQ), Growth Ratio Model (MRP), and Overlay Analysis. The LQ analysis shows that Lampung Province has 16 base sub-sectors and 36 non-base sub-sectors. Further analysis reveals that 10 sub-sectors are growing strongly both at the provincial and national levels, while 14 sub-sectors demonstrate stronger growth in Lampung compared to the same sub-sectors nationally. Through overlay analysis, six sub-sectors are identified as leading: livestock, oil, gas and geothermal mining, other mining and quarrying, the food and beverage industry, the machinery and equipment industry, and land transportation. These six sub-sectors are recommended to be prioritized as key drivers of Lampung Province's economic growth.